What the surgeon needs to know about percutaneous coronary intervention treatment of chronic total occlusions - Mitomo, Satoru; Demir, Ozan M.; Colombo, Antonio; Nakamura, Sunao; Chieffo, Alaide (Annals of Cardiothoracic Surgery, 2018)
Chronic total occlusion (CTO) accounts for 10–20% of lesions identified in coronary artery disease (CAD) patients. CTO percutaneous coronary intervention (PCI) is one of the most challenging of lesion subsets due to its technical difficulty, requiring specific operator expertise and equipment. There has been increased interest on CTO PCI evolving with the development of novel techniques and dedicated devices. Furthermore, in order to effectively and systematically utilize these techniques and devices, CTO PCI algorithms have been established. All of these developments have resulted in procedural success rates increasing to approximately 90%. In this review, we outline the evidence base for CTO PCI, conventional and contemporary CTO PCI techniques, CTO algorithms and outline integrated management strategies between cardiac surgeons and interventional cardiologists.